Screening of some plant materials used in South-West Algerian traditional medicine for their antibacterial activity - Fatehi Naima,; Houcine BENMEHDI,; Allali Hocine,; Oulednecir Nawal, (International Journal of Phytomedicine, 2017)
The initial introduction of new medicinal agents into the health care system sometimes, requires information beyond that is recorded in libraries relying instead, on reports available through traditions and healers within a society. This paper explored the antibacterial activity of aqueous and hydromethanolic extracts of nine folkloric medicinal plant from Bechar region (southwest Algeria) namely: A. nardus, A. schoenanthus, G. vulgaris, two species of H. scoparia green & red, P. laevigata, R. tripartita, T. gallica and T. nudatum, frequently used in the local traditional medicine. The antibacterial activity of different extracts were evaluated by using disc diffusion method agar and antibiotics susceptibility of ten selected microorganisms: seven reference strains, Bacillus cereus, Enterococcus faecalis, Staphylococcus aureus, Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, Salmonella typhi, and three clinically isolated strains, Escherichia coli (Urinary Tract Infection), Escherichia coli (Vaginal Infection) and Staphylococcus aureus (Skin Infection). The maximum antibacterial activity was recorded against the gram negative reference strains Pseudomonas aeruginosaand Escherichia coli with a maximum inhibition diameter of 15.6 ± 0.5 and 15.0 ± 1.4 mm respectively displayed by the aqueous extract of T. gallica, followed by the activity detected by the hydromethanolic extract of R. tripartita against the gram negative reference strain Pseudomonas aeruginosa (14.6±1.2 mm) and the aqueous and hydromethanolic extracts of R. tripartita against the gram negative reference strains Pseudomonas aeruginosa and Escherichia coli with a maximum inhibition diameter of 14.3 ± 2.0 and 14.3±0.5 mm, respectively. According to the present study, H. scoparia red, P. laevigata, R. tripartita, and T. gallicacan be served as broad spectrum antibiotic and used as a potent source of natural antibacterial agents by replacing commercially available synthetic drug that may have a large number of side effects.